2013
DOI: 10.1255/ejms.1241
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report: Development of a Piezoelectric Inkjet Dopant Delivery Device for an Atmospheric Pressure Photoionization Source with Liquid Chromatography/Mass Spectrometry

Abstract: This paper describes a simple, robust and integrated piezoelectric actuated printhead as a dopant delivery system for atmospheric pressure photoionization with liquid chromatography/mass spectrometry. The newly designed dopant delivery system avoids problems associated with traditional liquid delivery systems such as solvent immiscibility, backpressure and increased post-column dead volume issues. The performance of the new device was tested and evaluated using chlorobenzene as a dopant with a test mixture con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…3 More recently, it has been reported that fine droplets proved useful for mass spectrometry of complex bio-molecules in solution. 4 To date, numerous studies have been published concerning jet atomization achieved using either vibration or US. For instance, James et al 5 utilized a low-frequency vibration to study droplet ejection numerically, and elucidated that droplet ejection was due to a pinch-off phenomenon involving detachment from a main drop that was initially positioned on the surface of the vibrating solid wall.…”
Section: Introductionmentioning
confidence: 99%
“…3 More recently, it has been reported that fine droplets proved useful for mass spectrometry of complex bio-molecules in solution. 4 To date, numerous studies have been published concerning jet atomization achieved using either vibration or US. For instance, James et al 5 utilized a low-frequency vibration to study droplet ejection numerically, and elucidated that droplet ejection was due to a pinch-off phenomenon involving detachment from a main drop that was initially positioned on the surface of the vibrating solid wall.…”
Section: Introductionmentioning
confidence: 99%